Effect of n-3 and n-6 fatty acid supplementation on fetal, gestation and parturition in pregnant Sprague Dawley rats - Abdulbari Kassem, Amira; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Mohamed Mustapha, Noordin (Academic Journals, 2011)
The aim of this study was to evaluate the effect of different ratio of n-6:n-3 on gestation and parturition as well as to determine the hormone concentration on plasma of the pregnant rats. At the end of the trial period, blood plasma was collected and analysed for progesterone, estradiol and prostaglandin F2α hormone (PGF2α) concentrations, and fatty acids profile. The results indicated that the group with a very low ratio of n-6:n3 fatty acids (diet 1) showed increased concentration of progesterone in the plasma (P<0.05), while the group with high ratio of n6:n3 fatty acids (diet 3) with high arachidonic acid (AA) showed significantly (P<0.05) increased concentration of estradiol and PGF2α in the plasma. The n-3polyunsaturated fatty acids (PUFA) in plasma of diet 1 group were significantly (P<0.05) higher than the other treatment diet groups. The total n-6 PUFA was significantly higher (P<0.05) in diet 3 group as compared to diet 1 group. In contrast, the number of implanted embryos was significantly lower (P<0.05) in the diet 3 group at 15 days of gestation, while, the litter size were significantly lower in the diet 2 group and diet 3 group by 4.57 and 1.00 folds respectively, as compared to the control group (diet 4). In conclusion, for the rat with very low ratio on diet 1, the n-6:n-3 ratio satisfied the requirement for the growth of mother and fetuses but was inadequate for the normal process of parturition, probably through inadequate production of the prostaglandins involved.